Study of the High-temperature Synthesis of MgAl2O4 Spinel Refractory Raw Materials from Chromium Slag - Meng Jinxia; Chen Weiqing; Zhao Jizeng; Liu Li (High Temperature Materials and Processes, 2018)
To make use of chromium slag waste, this study examined the technology of the preparation of MgAl2O4 spinel refractory raw material by using chromium slag. The results showed that (1) using the traditional sintering process of synthetic spinel, the highest volume density was 3.14 g/cm3 and the lowest porosity rate was 9.16 %. With the increase of the proportion of MgO powder mixing, bulk density and porosity fluctuations, and which cannot meet the requirements of refractory raw materials. (2) For MgAl2O4 spinel prepared by the electric-melting process, the highest volume density was 3.27 g/cm3 and the lowest porosity rate was 8.78 %. Volume density and the porosity remained stable, and they are affected by MgO powder thus the blending ratio is very small, which can satisfy the requirements of refractory raw materials. (3) MgAl2O4 spinel prepared by the electric-melting method is superior to traditional MgAl2O4 spinel in terms of slag resistance and thermal shock resistance.